Bryophyte abundance, diversity and composition after retention harvest in boreal mixedwood forest. Issue 2 (14th September 2017) - Bartels, Samuel F.; Macdonald, S. Ellen; Johnson, Derek; Caners, Richard T.; Spence, John R.
Abstract: Variable‐retention harvest is widely recognized as an alternative to more intensive methods such as clear‐cutting. However, present information is inadequate to judge the impact of variable retention on biodiversity of indigenous forest organisms intolerant of canopy removal, such as forest‐inhabiting bryophytes. We examined how bryophyte species cover, richness, diversity and composition change with time in response to a broad range of dispersed retention harvest treatments (2% [clear‐cut], 10%, 20%, 50%, 75% retention of original basal area) contrasted with uncut controls [100% retention]) in broadleaf deciduous, mixedwood and conifer‐dominated boreal forests in North West Alberta, Canada. Bryophytes were studied in 432 permanent sample plots within 72 compartments before harvest and at 3, 6 and 11 years after harvest. Clear‐cut and lower (10% and 20%) retention levels resulted in lower cover and richness of bryophytes than in unharvested control compartments in mixed and conifer‐dominated forests, but less so in deciduous‐dominated forests, which generally supported low cover and richness. Species composition in each forest type varied along the gradient of harvesting intensity; clear‐cuts and lower levels of retention supported similar composition, as did control plots and those representing higher retention levels. Over time, the retention harvest treatments became more similar to uncut controls. Synthesis and applications . Variable‐retention harvests can better maintain bryophyte biodiversity in managed boreal mixedwood forests, as compared to clear‐cuts. We found the efficacy of retention harvest scaled with harvest intensity. Higher levels of retention better moderated the negative impacts of harvesting on bryophyte assemblages across all forest types. Our results suggest, however, that even 10% retention will facilitate faster post‐harvest recovery of bryophytes, as compared to clear‐cutting. Abstract : Variable‐retention harvests can better maintain bryophyte biodiversity in managed boreal mixedwood forests, as compared to clear‐cuts. We found the efficacy of retention harvest scaled with harvest intensity. Higher levels of retention better moderated the negative impacts of harvesting on bryophyte assemblages across all forest types. Our results suggest, however, that even 10% retention will facilitate faster post‐harvest recovery of bryophytes, as compared to clear‐cutting.